2012
DOI: 10.1007/s10616-012-9438-1
|View full text |Cite
|
Sign up to set email alerts
|

Increasing batch-to-batch reproducibility of CHO-cell cultures using a model predictive control approach

Abstract: By means of a model predictive control strategy it was possible to ensure a high batch-to-batch reproducibility in animal cell (CHO-cell) suspensions cultured for a recombinant therapeutic protein (EPO) production. The general control objective was derived by identifying an optimal specific growth rate taking productivity, protein quality and process controllability into account. This goal was approached indirectly by controlling the oxygen mass consumed by the cells which is related to specific biomass growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 11 publications
1
57
0
1
Order By: Relevance
“…The lack of more advanced online measurements hinders eventually the development of advanced process control tools that can improve the process efficiency. Despite the aforementioned obstacles, significant contributions have been reported in the control of mammalian cell cultures systems . Most of the presented studies rely either on an overwhelming amount of measurements or mathematical models and optimization procedures of excessive computational requirements.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The lack of more advanced online measurements hinders eventually the development of advanced process control tools that can improve the process efficiency. Despite the aforementioned obstacles, significant contributions have been reported in the control of mammalian cell cultures systems . Most of the presented studies rely either on an overwhelming amount of measurements or mathematical models and optimization procedures of excessive computational requirements.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Also seed train optimization can be an application of mechanistic models . Other applications are model‐based feeding profile optimization or model based monitoring and control of bioprocesses, e.g., by controlling the feed rate .…”
Section: Modeling Methodologiesmentioning
confidence: 99%
“…where J -control cost function, g; X -biomass concentration, g L -1 ; X pred -predicted biomass concentration, g L A model of the similar structure and MPC technique for Chinese hamster ovary (CHO) cell culture MPC were applied in research of Aehle et al 17 Kuprijanov et al 6 applied MPC for biomass concentration tracking. Further applications in chemical and refinery industrial processes were reported by Yüzgec et al 18 In the case investigated, the MPC non-convex problem is solved.…”
Section: Mpc Controller and Feeding Rate Control Algorithmmentioning
confidence: 99%